Proceedings of the 2nd Borobudur International Symposium on Humanities and Social Sciences, BIS-HSS 2020, 18 November 2020, Mag 2021
DOI: 10.4108/eai.18-11-2020.2311602
|View full text |Cite
|
Sign up to set email alerts
|

Halal Tourism in the Perspective of Indonesian Muslim Scholars: A Case Study in Magelang Regency

Abstract: The issue of halal is an important requirement for a Muslim, including tourism. In Indonesia, there has been a discourse on halal tourism recently, because of the needs of the Muslim community who are known as the majority of the population in Indonesia. Therefore, this study tries to look at the perspectives of Indonesian Moslem scholars regarding this issue. This research is a descriptive-qualitative field research. The research method uses in-depth interviews to see their views on the issue. From the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…Muqaddimah Ibn Khaldun became the first written work to specifically discuss social sciences (Goodman, 1972). Previous studies have revealed sharia tourism in the minds of Indonesian Muslim scholars, where most of the opinions of the scholars agree with the contribution of sharia tourism to the Muslim economy (Miswanto & Tohirin, 2021). This research refers to previous research conducted byAndhika(2019)regarding dynamic system models for simulating public policy formulation.…”
Section: Introductionmentioning
confidence: 83%
“…Muqaddimah Ibn Khaldun became the first written work to specifically discuss social sciences (Goodman, 1972). Previous studies have revealed sharia tourism in the minds of Indonesian Muslim scholars, where most of the opinions of the scholars agree with the contribution of sharia tourism to the Muslim economy (Miswanto & Tohirin, 2021). This research refers to previous research conducted byAndhika(2019)regarding dynamic system models for simulating public policy formulation.…”
Section: Introductionmentioning
confidence: 83%
“…This approach was undertaken to enhance the analysis and facilitate readers' comprehension of the strategies employed by the Indonesian government, Nahdlatul Ulama, and Muhammadiyah in enhancing Indonesia's national branding within the halal tourism sector. In this research, researchers will use the Miles and Huberman model (Miles and Huberman, 1992) where the Analysis Technique is divided into 3 paths, namely: data reduction, data presentation, and conclusions. In this study, researchers used the concept of nation branding as an analysis knife.…”
Section: Methodsmentioning
confidence: 99%
“…Padahal segala potensi wisata yang dimiliki bangsa ini sangat kaya dan beragam. Oleh karena itu, startegi dan kebijakan yang terstruktur, terencana, menjadi sangat penting untuk pengembangan pariwisata (Miswanto & Tohirin, 2020).…”
Section: Pendahuluanunclassified